2015
DOI: 10.1159/000431331
|View full text |Cite
|
Sign up to set email alerts
|

Renal Phospholipase A<sub>2</sub> Receptor in Hepatitis B Virus-Associated Membranous Nephropathy

Abstract: Objective: This study examined the expression of renal phospholipase A2 receptor (PLA2R) in idiopathic and secondary membranous nephropathy (MN). Methods: Patients with biopsy-proven MN and non-MN were enrolled. Renal PLA2R was examined using an anti-PLA2R antibody (anti-PLA2R-Ab), and circulating PLA2R-Ab was detected by indirect immunofluorescence. Results: Renal PLA2R was detected along the capillary loop in 84% patients with idiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 21 publications
2
84
1
3
Order By: Relevance
“…Circulating PLA2R antibodies seem to be specific for pMN [32-34]; however, they can also occur in secondary MN, especially the hepatitis B virus-related MN common in China [35]. The prevalence of positive antibodies varies between different diagnostic centers, from the highest prevalence of 82% [36] to the lower prevalences of 68% [37], 59% [38], and 69% [39], respectively, in China.…”
Section: The Autoimmune Disorders Of Pmnmentioning
confidence: 99%
“…Circulating PLA2R antibodies seem to be specific for pMN [32-34]; however, they can also occur in secondary MN, especially the hepatitis B virus-related MN common in China [35]. The prevalence of positive antibodies varies between different diagnostic centers, from the highest prevalence of 82% [36] to the lower prevalences of 68% [37], 59% [38], and 69% [39], respectively, in China.…”
Section: The Autoimmune Disorders Of Pmnmentioning
confidence: 99%
“…Glomerular depositions of PLA2R have been thought as specific findings of IMN. However, the significance of PLA2R for differentiation of IMN from HBV-MN is controversial because co-localized deposition with HBsAg has been reported from China (4). In the present case, we performed double immunofluorescence study with both of the antibodies against HBs-Ag and PLA2R, and found the co-localized deposition of them shown along the glomerular capillary walls.…”
Section: Discussionmentioning
confidence: 51%
“…However, the role of PLA2R in patients with HBV-MN is still unclear in Asian countries. Frequent co-localization of PLA2R and HBV antigens are reported mainly from China (4). We report the case of PLA2R-positive HBV-MN that was remitted with entecavir after a relapse during the treatment with lamivudine.…”
Section: Introductionmentioning
confidence: 89%
“…Although initial reports showed ,5% of patients with HBVassociated MN having a positive assay for anti-PLA2R (12), a recent study indicated contradictory findings with 64% of HBV patients showing anti-PLA2R (13). The study also demonstrated the presence of HBV antigens colocalizing with anti-PLA2R antibody confirming the possible association of these two findings.…”
Section: Membranous Nephropathymentioning
confidence: 52%